PENGARUH PENGETAHUAN DAN PERSEPSI MAHASISWA PERBANKAN SYARIAH UMSU TERHADAP MINAT BERKARIR DI BANK SYARIAH - Rahmayu Hartini (Al-Muhtarifin: Islamic Banking and Islamic Economic Journal, 2026)
This study aims to determine and analyze the effect of knowledge and perceptions of UMSU Islamic banking students on career interests in Islamic banks. This study used primary data using a questionnaire method for 72 respondents using probability sampling technique. This study uses a model with a multiple linear regression analysis approach to determine the effect of knowledge and perceptions of UMSU Islamic banking students on career interest in Islamic banking. The results of the study show that knowledge appears to have a positive and significant effect on interest in a career in Islamic banks, perceptions have a positive and significant effect on interest in a career in Islamic banks. Simultaneously the knowledge and perceptions of UMSU Islamic banking students have a positive and significant effect on career interest in Islamic banks with an adjusted R-Square coefficient of determination of 73.4%.